2020
DOI: 10.1038/s41523-020-00190-9
|View full text |Cite
|
Sign up to set email alerts
|

ARe we there yet? Understanding androgen receptor signaling in breast cancer

Abstract: The role of androgen receptor (AR) activation and expression is well understood in prostate cancer. In breast cancer, expression and activation of AR is increasingly recognized for its role in cancer development and its importance in promoting cell growth in the presence or absence of estrogen. As both prostate and breast cancers often share a reliance on nuclear hormone signaling, there is increasing appreciation of the overlap between activated cellular pathways in these cancers in response to androgen signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 220 publications
(307 reference statements)
2
43
0
Order By: Relevance
“…Interestingly, MOE:PTEN shRNA induced testosterone when grown in proximity of the ovary, but were not susceptible to androgen-induced proliferation, nor were they effected by bicalutamide. This data is consistent with existing studies that have examined the interactions between PTEN and AR in breast and prostate cancer showing that PTEN and AR directly interact and that loss of PTEN, and commensurate increased PI3K activity, reduces AR signaling [50][51][52]. While our data suggests that PTEN deficient tubal cells may themselves be insulated from the pro-proliferative effects of ovarian androgenic secretions, the surrounding epithelium and earlier precursor lesions such as SCOUTs remain susceptible.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, MOE:PTEN shRNA induced testosterone when grown in proximity of the ovary, but were not susceptible to androgen-induced proliferation, nor were they effected by bicalutamide. This data is consistent with existing studies that have examined the interactions between PTEN and AR in breast and prostate cancer showing that PTEN and AR directly interact and that loss of PTEN, and commensurate increased PI3K activity, reduces AR signaling [50][51][52]. While our data suggests that PTEN deficient tubal cells may themselves be insulated from the pro-proliferative effects of ovarian androgenic secretions, the surrounding epithelium and earlier precursor lesions such as SCOUTs remain susceptible.…”
Section: Discussionsupporting
confidence: 92%
“…The prognostic value of AR expression in breast cancer has been evaluated in multiple breast cancer cohorts (14,(23)(24)(25)(26). Steroid hormone nuclear receptors like estrogen and androgen receptors often crosstalk and influence the action of each other (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…T probably exerts its action through its union to the androgen receptor (AR). AR is expressed in 15–30% of TNBC, and some studies have suggested that AR might function in place of ER in its absence [ 32 ]. Contrarily, when cells were treated with STX-64, DHT secretions were significantly diminished.…”
Section: Discussionmentioning
confidence: 99%